Syndecan-4 is More Sensitive in Detecting Hypertensive Left Ventricular Diastolic Dysfunction in 2K2C Rats - Wenyue Dai; Yanqiu Liu; Fengjuan Yao; Wei Li; Jia Liu; Cuiling Li; Donghong Liu (International Journal of Hypertension)
Objective. The aim of this study was to investigate the changes of syndecan-4 (SDC-4) during the hypertensive period in two kidney-two clip (2K2C) hypertension rats and compare them to brain natriuretic peptide (BNP) and the echocardiographic parameters for diastolic function evaluation in the rat model of 2K2C hypertension. Methods. A total of 36 Sprague–Dawley (SD) rats were used in this study. Hypertension was induced in 21 by 2K2C surgery, and 15 were sham-operated. Both the 2K2C hypertension group (n = 21) and the sham-operated group (n = 15) were equally divided into 3 subgroups according to the schedules (week 4, week 8, and week 12). Serum SDC-4 and BNP were detected by ELISA, and echocardiography indexes were acquired. Results. The level of SDC-4 and cardiac fibrosis increased gradually as the experiment was processed, and BNP, Tei index, and E/E′ followed to be raised as high blood pressure was maintained after four weeks in the 2K2C hypertension rats. In the earlier 4 weeks, only SDC-4 and cardiac fibrosis were significantly increased in 2K2C hypertensive rats in comparison with normotensive rats. And it was shown that SDC-4 was positively correlated with BNP level during the entire study (r = 0.762, p<0.01). Conclusion. SDC-4 increases gradually during the process of diastolic dysfunction in 2K2C hypertensive rats. SDC-4 is the earliest biomarker reflecting diastolic dysfunction in this model, superior to E/E′ and the Tei index. Our results indicate that serum SDC-4 could act as an early biomarker to show diastolic dysfunction.